A Pareto investigation on critical barriers in green supply chain management. Issue 2 (3rd April 2019) - Kaur, Jasneet; Sidhu, Ramneet; Awasthi, Anjali; Srivastava, Samir K.
ABSTRACT: More and more organizations are involved in green supply chain practices to sustain business market competition, achieve customer loyalty, improve brand image, and minimize negative environmental impacts. Examples of these practices are green design, green purchasing, green manufacturing, green packaging, green logistics, and green marketing. In this paper, we investigate barriers in green supply chain management and identify the 'critical' or 'vital' using Pareto analysis. The data for green supply chain barriers is extracted using literature review and expert surveys. Pareto analysis is conducted on the two data sources to identify the priority barriers and the common barriers are determined as 'vital few'. The results of our study yield 'difficulty in transforming positive environmental attitudes into action' and 'lack of awareness about reverse logistics adoption' as the top priority barriers followed by 'high cost of hazardous waste disposal', 'perception of "out of responsibility" zone', 'lack of R&D capability on ESER (Environmental and Sustainability Education Research)', and 'lack of corporate social responsibility'. These barriers are related to awareness, cost, commitment and resources. Interested organizations should therefore put focus on these barriers to make green supply chain practices successful.